Položaj in podoba sodobnega ljubiteljskega gledališča na Slovenskem - Troha, Gašper (Amfiteater (Ljubljana), 2020)
The article explores amateur theatre in Slovenia and developments in this field after 1991. Although significant social and political changes took place in 1991, the analysis shows that the system of state financing and local community support for amateur theatre remains virtually the same as established in the period between 1945 and 1991. The same goes for educational and professional support of amateur theatre and amateur culture as a whole. The recent empirical analysis of amateur culture carried out by the Union of Cultural Societies of Slovenia (2019) shows that the most significant shift can be detected in the nature of the functioning of amateur theatre. While amateur culture used to allow professional artists the opportunity to try out and develop alternative theatre practices as well as to express dissident ideas, this is no longer the case. After 1991, such practices mostly moved over to the strong NGO sector, which is funded directly by the state and offers a space in which alternative theatre can develop.
Keywords: alternative theatre; alternativno gledališče; amateur culture; amateur theatre; cultural policy; financing of culture; financiranje kulture; kulturna politika; ljubiteljska kultura; ljubiteljsko gledališče